GAME EDUKASI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN ERA DIGITAL DI SMP NEGERI 11 MANADO - Sarina Bawole; Olivia Cherly Wuwung; Subaedah Luma (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2026)
This research aims to analyze and describe the use of educational games as a learning medium for Christian Religious Education in the Digital Era at SMP Negeri 11 Manado. This study employs a qualitative research method with a descriptive-analytic approach. Observation, interviews, and literature studies were conducted to collect data and revealed the following findings: Teachers have previously used technology, but mostly relied on conventional media which make students are not highly motivated to participate in the learning process. The use of educational games such as Wordwall application as a learning medium can improve students’ participation and motivation in the learning process. Although the implementation of the educational games at first faced several challenges that hinders learning such as limited internet quota and the poor condition of the device used by some students, the problems can be solved by the school support such as the availability of School Wi-Fi and electrical power sources or sockets in several corners of classrooms. Thus, the improvements in the teaching and learning process can be observed through the use of educational games. One of the significant outcomes is the increased enthusiasm of students to participate actively in classroom activities. This ultimately contributes to improving the quality of education at SMP Negeri 11 Manado